Latarjet procedure versus iliac crest autograft transfer for anterior shoulder instability: a systematic review and meta-analysis of comparative studies - Lang Li; Bofang Zeng; Meng Ding; Sha Wan; Kefu Lin; Zhen Tian (Journal of Orthopaedic Surgery and Research)
Abstract Background Anterior shoulder instability with glenoid bone loss presents a challenge in orthopedic surgery. The Latarjet and iliac crest bone graft transfer (ICBGT) procedures are commonly employed for its management, but direct comparative evidence is insufficient. Methods Following PRISMA guidelines, a comprehensive search of PubMed, EMBASE, Cochrane Library, and Web of Science was conducted. Randomized controlled trials (RCTs) and cohort studies directly comparing the Latarjet and ICBGT procedures were included. Primary outcomes included postoperative recurrent instability, apprehension test, and complications, while secondary outcomes comprised Rowe score, Subjective Shoulder Value (SSV), pain level assessed by visual analogue scale (VAS), range of motion (ROM), and radiologic outcomes. Quality assessment was performed using RoB2 and MINORS tools. The weighted mean difference (WMD) for continuous variables and odds ratio (OR) for dichotomous variables were calculated, along with 95% confidence intervals (CIs). Meta-analysis was performed using RevMan 5.4.1 software. Results A total of 6 studies with 409 patients were included. There was no significant difference in postoperative recurrent instability (OR, 1.33; 95% CI, 0.44 to 4.03; P = 0.61), positive apprehension test (OR, 0.78; 95% CI, 0.20 to 3.10; P = 0.73), revision surgery (OR, 2.06; 95% CI, 0.74 to 5.71; P = 0.16), mild complications (OR, 0.49; 95% CI, 0.23 to 1.06; 0.07), SSV (WMD, -1.94; 95% CI, -3.94 to 0.06; P = 0.06) or VAS score (WMD, 0.15; 95% CI, -0.17 to 0.47; P = 0.36) between the two procedures. The ICBGT group exhibited statistically superior Rowe scores (WMD, -3.10; 95% CI, -5.10 to -1.10; P = 0.002), as well as improved external (WMD, -5.32; 95% CI, -7.30 to -3.30; P < 0.001) and internal rotation (WMD, -5.11; 95% CI, -6.76 to -3.45; P < 0.001). However, these differences did not surpass the minimal clinically important difference (MCID). Radiological evaluations showed that the ICBGT procedure had statistically better outcomes in immediate glenoid augmentation, preservation and reduced fatty degeneration of the subscapularis (SSC) tendon, and graft remodeling at short-term follow-up. Conclusions The ICBGT procedure showed statistically superior Rowe scores and range of motion, but these differences may not be clinically significant. Both procedures had comparable outcomes in recurrent instability, apprehension test results, revision surgery, mild complications, SSV, and pain levels. ICBGT appears to offer advantages in glenoid augmentation and SSC preservation at short-term follow-up. PROSPERO registration ID CRD42024586157.